The Political Orientation of the Hadhrami Community in the 2019 Presidential Election in Palembang City (A Study in Al-Munawar Village and Assegaf Village) - Kharisma, Luffi (Ampera: A Research Journal on Politics and Islamic Civilization, 2023)
Historically, the Hadhrami community originated in the Hadhramaut region of South Yemen, where in the 19th century, they migrated throughout Asia for trade and to spread Islam. Evidence suggests that the Hadhrami community has been present in Palembang through trade routes since the establishment of the first Hadhrami Arab community village in the Kuto Gawang area in 1659, as indicated by a Dutch-made map. In addition to acculturating with indigenous people, they are actively involved in political activities, including elections. Tis study investigates the political orientation of the Hadhrami community in Al-Munawar Village and Assegaf Village during the 2019 presidential election in Palembang City, along with the factors influencing their political stance. The research approach adopted in this thesis is descriptive-qualitative. Primary data were gathered through direct interviews with representatives from each village, while secondary data were obtained from literature reviews and documents. Findings reveal that during the 2019 presidential election in Palembang City, both Al-Munawar Village and Assegaf Village of the Hadhrami community upheld the principle of freedom of choice without external or internal interference. While the overall political orientation of the Hadhrami community remained largely consistent, nuances were observed between the two villages. Al-Munawar Village demonstrated an evaluative political orientation, emphasizing the importance of scrutinizing the background of presidential candidates. Conversely, Assegaf Village's political orientation was cognitive, focusing on the perceived image of the candidate. The factors influencing the political orientation of the Hadhrami community in Al-Munawar Village and Assegaf Village during the 2019 presidential election in Palembang City vary slightly. Al-Munawar Village's political orientation is attributed to a lack of political education and prioritization of economic needs over active electoral participation. Meanwhile, Assegaf Village's political orientation is influenced by an understanding of the prevailing political landscape and the desire for economic stability, which shapes their political stance.